A problem with formal initial conditions for differential equations with constant pseudodifferential coefficients - Il'kiv, V. S. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We establish conditions for the unique existence of a solution of a problem with formal initial conditions. We investigate the problem of its solvability in the case where a solution is not unique.